2015
DOI: 10.3354/meps11385
|View full text |Cite
|
Sign up to set email alerts
|

Community metabolism in shallow coral reef and seagrass ecosystems, lower Florida Keys

Abstract: Diurnal variation of net community production (NEP) and net community calcification (NEC) were measured in coral reef and seagrass biomes during October 2012 in the lower Florida Keys using a mesocosm enclosure and the oxygen gradient flux technique. Seagrass and coral reef sites showed diurnal variations of NEP and NEC, with positive values at near-seafloor light levels >100-300 µEinstein m −2 s −1 . During daylight hours, we detected an average NEP of 12.3 and 8.6 mmol O 2 m −2 h −1 at the seagrass and coral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 68 publications
(108 reference statements)
1
20
0
Order By: Relevance
“…The gradient flux approach measures the mean gradient in momentum and chemical properties of interest in the benthic boundary layer (BBL) to calculate the bottom flux. This approach has been successfully applied in reef environments to quantify momentum [ Reidenbach et al ., ], phytoplankton [ Genin et al ., ], and O 2 fluxes (thus NCP) [ McGillis et al ., ; Turk et al ., ]. The NCP rates based on this approach have been shown to agree well with estimates based upon closed in situ benthic enclosures [ Yates and Halley , ; Yates et al ., ].…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…The gradient flux approach measures the mean gradient in momentum and chemical properties of interest in the benthic boundary layer (BBL) to calculate the bottom flux. This approach has been successfully applied in reef environments to quantify momentum [ Reidenbach et al ., ], phytoplankton [ Genin et al ., ], and O 2 fluxes (thus NCP) [ McGillis et al ., ; Turk et al ., ]. The NCP rates based on this approach have been shown to agree well with estimates based upon closed in situ benthic enclosures [ Yates and Halley , ; Yates et al ., ].…”
Section: Introductionmentioning
confidence: 66%
“…An exponential relationship between PAR and NCP is well established [ Platt et al ., ; Gattuso et al ., ; Long et al ., ; Turk et al ., ], though there is less consensus on the shape of the relationship between PAR and NCC. Examples for linear [ Barnes and Devereux , ; Gattuso et al ., ; Falter et al ., ; Albright et al ., ] and exponential [ Gattuso et al ., ; Boucher et al ., ; Cuet et al ., ] relationships have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…A previous analysis of community metabolism that included productivity and calcification of the same patch reef and seagrass areas [70] showed that lower PAR values during storms can lower these metabolic rates for hours, while during periods of higher daylight illumination, calcification and productivity rates increased. Our surveys captured the impact of two strong thunderstorms in October, which limited light reaching the ocean's surface and also increased the concentration of suspended materials in the water.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-fourhour measurements of oxygen and carbon parameters have also shown variability throughout the day and night for coral reef systems (Albright et al, 2013;Yates et al, 2007). In contrast, nighttime rates stayed constant for seagrass habitats in a study by Turk et al (2015). Since nighttime measurements were conducted close to sunset, respiration rates were overestimated due to light-enhanced respiration.…”
Section: Community Primary Productivitymentioning
confidence: 94%